The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/jacs.9b05539
|View full text |Cite
|
Sign up to set email alerts
|

Triggered Gate Opening and Breathing Effects during Selective CO2 Adsorption by Merlinoite Zeolite

Abstract: Contents S1. Synthesis and Initial Characterisation S2. Crystallographic details of the refined hydrated Na-, (K-and K, Hand nd Cs-MER S3. Structural response to dehydration S4. Adsorption studies S5. In situ laboratory PXRD of M-MER with adsorbed CO2 S6. Crystallographic details of the refined dehydrated solids with adsorbed CO2 S7. CO2/CH4 separation and breakthrough curves S8. Kinetic measurements using the Zero Length Column technique S9. K,H-MER zeolite structural and adsorption results S2 S1. Synthesis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
112
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 97 publications
(126 citation statements)
references
References 38 publications
11
112
0
Order By: Relevance
“…In most cases structural modifications are triggered by a specific adsorbate concentration, but cases of temperature and pressure induced transitions have also been reported . Structural changes can manifest in number of ways including change of the cage volume, breathing (Barthelet et al 2002) and gate opening (Lozinska et al 2012;Georgieva et al 2019). The possibility of triggering a controlled change in the kinetic and/or equilibrium selectivity opens a range of unexplored opportunities both from the materials and processes point of view.…”
Section: Systems With Structural Changes Due To Adsorptionmentioning
confidence: 99%
“…In most cases structural modifications are triggered by a specific adsorbate concentration, but cases of temperature and pressure induced transitions have also been reported . Structural changes can manifest in number of ways including change of the cage volume, breathing (Barthelet et al 2002) and gate opening (Lozinska et al 2012;Georgieva et al 2019). The possibility of triggering a controlled change in the kinetic and/or equilibrium selectivity opens a range of unexplored opportunities both from the materials and processes point of view.…”
Section: Systems With Structural Changes Due To Adsorptionmentioning
confidence: 99%
“…By blocking the pore entries, the extra‐framework cations selectively provide access for molecules to the zeolite channels and cages depending on the nature of the molecules [6] . A high selectivity towards CO 2 over CH 4 for small‐pore zeolites with RHO, MER, and CHA type framework has been observed, indicating that the cation gating effect permits the uptake of CO 2 but not CH 4 [7, 8] …”
Section: Figurementioning
confidence: 99%
“…While merlinoite is rarely found in nature, several synthetic analogues like K‐M and Linde W have been reported and typically characterized with the Si/Al ratio range of 1.5–2.4 [8] . Wright and co‐workers have recently reported that CO 2 adsorption mechanism on the Na + , K + , and Cs + forms of an MER zeolite with Si/Al=3.8 synthesized using tetraethylammonium (TEA + ) ions as an organic structure‐directing agent (SDA), together with K + , is based on the breathing effect [7b] …”
Section: Introductionmentioning
confidence: 99%